Endogenous fungal endopthalmitis treated with intravitreal caspofungin in a COVID-19 recovered patient: A case report - Chinmay Nakhwa (Indian Journal of Ophthalmology, 2021)
We present a case of endogenous fungal endophthalmitis in a nondiabetic, nonhypertensive patient who recovered from COVID-19 infection. Endogenous fungal endophthalmitis in an immunocompetent individual is quite uncommon. The organism in our patient was resistant to amphotericin and voriconazole and was successfully treated with intravitreal caspofungin. The rarity of an opportunistic nosocomial infection in an immunocompetent person with a drug-resistant organism prompted us to write this report.